An Analysis Code Mixing Of “Go Visit Daddy In Canberra” By The Connell Twins Youtube Channel - Yantris, Rianty Dwi; Sembiring, Rony Arahta; Sihite, Jubilezer (JUPE : Jurnal Pendidikan Mandala, 2024)
This study discusses the phenomenon of code mixing in everyday communication, which is increasingly important in multilingual societies. Although there are many studies on code mixing, none have reviewed specifically on the YouTube channel "The Connell Twins". The purpose of this study is to identify the types and functions of code mixing used in the video "Go Visit Daddy in Canberra". The method used includes qualitative analysis based on Charlotte Hoffman's theory. The main findings indicate that there are various types of code mixing, including intra-sentential and intra-lexical, as well as the social functions underlying their use. The results of the study showed that there were 37 cases of Intra-sentential code mixing, 2 cases of Intra-Lexical code mixing, and 1 case of Involving pronunciation changes. In conclusion, this study provides new insights into language use in social and cultural contexts, and improves understanding of the dynamics of bilingual communication among the younger generation. This study is expected to be a reference for further studies in the field of sociolinguistics.